Deformation and fatigue of tough 3D printed elastomer scaffolds processed by fused deposition modeling and continuous liquid interface production. (November 2017) - Miller, Andrew T.; Safranski, David L.; Wood, Catherine; Guldberg, Robert E.; Gall, Ken
Abstract: Polyurethane (PU) based elastomers continue to gain popularity in a variety of biomedical applications as compliant implant materials. In parallel, advancements in additive manufacturing continue to provide new opportunities for biomedical applications by enabling the creation of more complex architectures for tissue scaffolding and patient specific implants. The purpose of this study was to examine the effects of printed architecture on the monotonic and cyclic mechanical behavior of elastomeric PUs and to compare the structure-property relationship across two different printing approaches. We examined the tensile fatigue of notched specimens, 3D crosshatch scaffolds, and two 3D spherical pore architectures in a physically crosslinked polycarbonate urethane (PCU) printed via fused deposition modeling (FDM) as well as a photo-cured, chemically-crosslinked, elastomeric PU printed via continuous liquid interface production (CLIP). Both elastomers were relatively tolerant of 3D geometrical features as compared to stiffer synthetic implant materials such as PEEK and titanium. PCU and crosslinked PU samples with 3D porous structures demonstrated a reduced tensile failure stress as expected without a significant effect on tensile failure strain. PCU crosshatch samples demonstrated similar performance in strain-based tensile fatigue as solid controls; however, when plotted against stress amplitude and adjusted by porosity, it was clear that the architecture had an impact on performance. Square shaped notches or pores in crosslinked PU appeared to have a modest effect on strain-based tensile fatigue while circular shaped notches and pores had little impact relative to smooth samples. When plotted against stress amplitude, any differences in fatigue performance were small or not statistically significant for crosslinked PU samples. Despite the slight difference in local architecture and tolerances, crosslinked PU solid samples were found to perform on par with PCU solid samples in tensile fatigue, when appropriately adjusted for material hardness. Finally, tests of samples with printed architecture localized to the gage section revealed an effect in which fatigue performance appeared to drastically improve despite the localization of strain.